Incidence of Primary and Second Cancers in Renal Transplant Recipients: A Multicenter Cohort Study. Issue 1 (11th October 2012) - Tessari, G.; Naldi, L.; Boschiero, L.; Minetti, E.; Sandrini, S.; Nacchia, F.; Valerio, F.; Rugiu, C.; Sassi, F.; Gotti, E.; Fonte, L.; Talamini, G.; et al.
<x xml:space="preserve">Abstract</x> Limited data exist about cancer prognosis and the development of second cancers in renal transplant recipients. In a retrospective cohort study on 3537 patients incidence rates of the first and, if any, of a second cancer, and standardized incidence ratios [SIR (95% CI)] were computed. Two hundred and sixty‐three (7.5%) patients developed a NMSC, and 253 (7.2%) another type of cancer after a median follow‐up of 6.5 and 9.0 years, respectively. A statistically significant excess risk, if compared to an age‐ and sex‐matched reference general population, was observed for Kaposi sarcoma and NMSC, followed by non‐Hodgkin lymphoma and carcinoma of cervix uteri; a small number of unusual cancers such as tumors of the salivary glands, small intestine and thyroid also were detected at a level worthy of additional scrutiny. Ten‐year survival rate of all noncutaneous cancers was 71.3%, with lower rates for lung carcinoma and non‐Hodgkin lymphoma (0% and 41.7%, respectively). Patients with NMSC had an increased risk of developing a second NMSC [SIR 8.3 (7.0–10.0)], and patients with a primary noncutaneous cancer had increased risk of developing a second noncutaneous cancer [SIR 1.8 (1.2–2.8)], if compared to the whole cohort. Our study underscore that the high risk of primary and second cancer in renal transplant recipients, including unusual cancers.